Recurrent Mycobacterium chelonae Skin Infection Unmasked as Factitious Disorder Using Bacterial Whole Genome Sequence Analysis. (22nd October 2020) - Flohr, Sarah; Ramette, Alban; Agyeman, Philipp K A; Duppenthaler, Andrea; Scherer, Cordula; Keller, Peter M; Aebi, Christoph
Abstract: Mycobacterium chelonae infections usually resolve with adequate therapy. We report the case of an adolescent with a chronic and progressive M chelonae infection refractory to combined antimicrobial and surgical therapy. Whole genome sequence analysis of consecutive isolates distinguished reinfection from recurrence and contributed to the diagnosis of a factitious disorder.